Improving Mathematical Problem-Solving Abilities Through An Open-Ended Approach In Grade VI Of Mi Maraqitta’limat Anyar In The 2025/2026 Academic Year - Rusman Hadi (JUPE : Jurnal Pendidikan Mandala, 2026)
The purpose of this study was to improve the mathematical problem-solving skills of sixth-grade students at MI Maraqitta’limat Anyar using an open approach. The research approach used was CAR, which was conducted over two cycles. Participants in this study were 15 sixth-grade students from MI Maraqitta’limat Anyar. The tools used consisted of observation forms, problem-solving tests, and documentation. The results showed that the use of an open approach successfully improved students' abilities in solving mathematical problems. This improvement was reflected in the increase in students' test scores, rising from 20% in the pre-cycle to 46.7% in the first cycle, and reaching 80% in the second cycle. In short, the open method proved successful in encouraging students to engage in creative thinking and discover various strategies to solve problems